Mengelola transisi lintas budaya: Strategi dukungan kelembagaan bagi mahasiswa internasional di perguruan tinggi - Wu Jiewei; Aan Komariah; Dedy Achmad Kurniady; Sururi Sururi (Universitas Pendidikan Indonesia, 2026)
International students often encounter unfamiliar pedagogical systems, cultural dissonance, or marginalization that can affect them academically and psychologically. This article systematically reviews Scopus-indexed articles (2020-2026) that address institutional support for international students during cross-cultural transitions in higher education, following the PRISMA 2020 reporting procedure. A narrative thematic analysis was conducted on 14 studies that met the inclusion criteria. The synthesis of findings indicates that cross-cultural adaptation is co-constructed by individual capabilities such as cultural intelligence, coping, motivation, and communication competencies, as well as institutional conditions that support access, belonging, and cultural sensitivity. Effective academic and social support is reflected in inclusive learning environments, connectedness to the host community, and coordinated administrative support. Furthermore, recent findings emphasize the importance of the digital ecology as an additional layer of support that facilitates student access, inclusion, and psychological well-being. The results of this review inform the design of a systematically integrated, phased support model and highlight the need for longitudinal, multi-site evaluation.